2018
DOI: 10.1037/xlm0000527
|View full text |Cite
|
Sign up to set email alerts
|

The dimensionality of reasoning: Inductive and deductive inference can be explained by a single process.

Abstract: Three-experiments examined the number of qualitatively different processing dimensions needed to account for inductive and deductive reasoning. In each study, participants were presented with arguments that varied in logical validity and consistency with background knowledge (believability), and evaluated them according to deductive criteria (whether the conclusion was necessarily true given the premises) or inductive criteria (whether the conclusion was plausible given the premises). We examined factors inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…More importantly for our current interest in instructions, Experiment 1 did not replicate the effects sometimes observed that 1) validity has a larger effect on deduction than induction and 2) believability has a larger effect on induction than deduction (e.g., Hayes et al, 2018;Rips, 2001;Rotello & Heit, 2009).…”
Section: Instructions Validity and Believability Effectsmentioning
confidence: 76%
See 4 more Smart Citations
“…More importantly for our current interest in instructions, Experiment 1 did not replicate the effects sometimes observed that 1) validity has a larger effect on deduction than induction and 2) believability has a larger effect on induction than deduction (e.g., Hayes et al, 2018;Rips, 2001;Rotello & Heit, 2009).…”
Section: Instructions Validity and Believability Effectsmentioning
confidence: 76%
“…Therefore, future experiments could stick with induction and deduction judgments as the core dependent variables or tasks, but manipulate other combinations of independent variables, such as the emotional content of arguments, argument difficulty, working memory, cognitive ability, or decision time. Note however, that Hayes et al (2018) examined working memory load, working memory capacity, and decision time for induction and deduction judgments about simple arguments, and still found no evidence to support multiple processes based on state-trace analysis.…”
Section: Alternative Tests Of the Independent-1d Modelmentioning
confidence: 85%
See 3 more Smart Citations